The Immediate Pain-Relieving Effects of Non-Thermal CO2 Laser Therapy on Genital Ulcers of Behcet’s Disease: A Case Report - Zand, Nasrin; Mansouri, Parvin; Rezaee Khiabanloo, Samad; Fateh, Mohsen; Ataie Fashtami, Leila; Safaee Naraghi, Zahra; Shirkavand, Afshan (Journal of Lasers in Medical Sciences, 2020)
Behçet’s disease (BD) is a chronic, relapsing, systemic vasculitis of unknown etiology. Oral and genital aphthous ulcers are considered as the hallmarks of BD. The genital ulcers of BD may be extremely painful and often refractory to multiple treatments. In addition, they exert a negative impact on the patient’s quality of life. Some investigations have demonstrated the significant and immediate pain-relieving effects of NTCLT (non-thermal CO2 laser therapy) on some oral lesions with no visible adverse effects. In this paper, we report a case of BD whose painful genital ulcers were irradiated with NTCLT and the patient’s pain caused by the ulcers relieved immediately and significantly with no visible complications.